2020
DOI: 10.1111/jcal.12489
|View full text |Cite
|
Sign up to set email alerts
|

Is contextual animation needed in multimedia learning games for children? An eye tracker study

Abstract: The present study investigates affective‐motivational, attention, and learning effects of unexplored emotional design manipulation: Contextual animation (animation of contextual elements) in multimedia learning game (MLGs) for children. Participants (N = 134; Mage = 9.25; Grades 3 and 4) learned either from an experimental version of the MLG with a high amount of contextual animation or from an identical MLG with no contextual animation (control). Children strongly preferred (χ2 = 87.04, p < .001) and found th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 55 publications
0
1
0
Order By: Relevance
“…In the reviewed studies, seductive details were mostly found to be the factor differentiating cognitive processing of multimedia information. Eye-tracking metrics contribute to emotional design studies in terms of providing objective data beyond the data collected as self-reports with scales and tests (Javora et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In the reviewed studies, seductive details were mostly found to be the factor differentiating cognitive processing of multimedia information. Eye-tracking metrics contribute to emotional design studies in terms of providing objective data beyond the data collected as self-reports with scales and tests (Javora et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the actual effect of game-derived enjoyment, or similar affective-motivational construct, on time-on-task was examined insufficiently. For example, a series of lab studies suggested that better-looking artistic design for a children’s educational game increased preference for interfacing with the better-looking game version, but not learning outcomes when the time-on-task was fixed ( Javora et al, 2019 , 2021a , b ). The studies were inconclusive though with regards to the following question: what would happen had the children been allowed to learn from the game as long as they would have liked?…”
Section: Introductionmentioning
confidence: 99%